Acoustic Particle Detection with the ANTARES Detector. (18th March 2010) - Richardt Richardt, C. C.; Anton Anton, G. G.; Graf Graf, K. K.; Hößl Hößl, J. J.; Katz Katz, U. U.; Lahmann Lahmann, R. R.; Neff Neff, M. M.
Abstract : The (Antares Modules for Acoustic Detection Under the Sea) AMADEUS system within the (Astronomy with a Neutrino Telescope and Abyss environmental RESsearch) ANTARES neutrino telescope is designed to investigate detection techniques for acoustic signals produced by particle cascades. While passing through a liquid a cascade deposits energy and produces a measurable pressure pulse. This can be used for the detection of neutrinos with energies exceeding 10 18 eV. The AMADEUS setup consists of 36 hydrophones grouped in six local clusters measuring about one cubic meter each. This article focuses on acoustic particle detection, the hardware of the AMADEUS detector and techniques used for acoustic signal processing.